Segredo de justiça ou justiça secreta: decretação do segredo de justiça nos processos relacionados ao crime de tráfico de pessoas - Gama, Ana Patrícia da Costa Silva Carneiro (2023)
The principle of publicity in criminal proceedings is now recognized as a fundamental human right due to its close relationship with the principle of fair trial, democracy, and the rule of law. Going beyond a mere formality, this principle is essential for achieving substantive justice. However, publicity may be waived in exceptional cases to the extent strictly necessary. Therefore, uncontrolled and implementation of these limitations with no transparency by the courts can lead to situations of secret justice capable of undermining this social achievement. Focused on reflecting on the hypotheses of legitimate restriction to the scope of protection of this principle and the consequences arising from its breach, this doctoral thesis focuses on the principle of publicity in proceedings dealing with human trafficking, since such proceedings typically involve scenarios with the potential to justify the taking of this exceptional measure. The question is: is the (non) imposition of secrecy in these proceedings in line with current constitutional and international guidelines? Articles 5, LX and 93, IX, of the Brazilian Constitution of 1988 provide for the possibility of restricting publicity in the face of the right to privacy. In the case of a conflict between fundamental rights and the absence of a constitutional, infra-constitutional, or treaty rule that expressly determines the suppression of procedural publicity in favor of privacy in the case of investigation of human trafficking, the decision to impose secrecy in the proceedings relating to the crime must have constitutional motivation and observe the proportionality rule, according to Robert Alexy's understanding and the respective adaptations of Virgílio Afonso da Silva to the internal legal order, similar to other cases involving a conflict of fundamental rights and that are the subject of decisions emanating from the higher courts of the Brazilian justice system. In this regard, ten judicial proceedings dealing with the practice of the crime typified in Article 149-A of the Brazilian Penal Code, which were mainly processed in the Regional Federal Courts of Brazil, were analyzed to verify the legal and factual precepts used to decide on the application of the general rule of procedural publicity or the exception of secrecy in the cases analyzed, through the data collected on their official websites, as well as on the Jusbrasil.com jurisprudential search site. The study was based on semantic, historical, legal, and jurisprudential analyses, provided by a bibliographic survey of the academic production that surrounds the theme; secondary data about the object of study; and documentary review of judicial proceedings dealing with human trafficking, enabling a theoretical-practical activity, which characterizes the research as exploratory and descriptive. Based on doctrinal and documentary analysis, it was demonstrated that there is no reasonable and coherent systematization, imbued with constitutional motivation, in the imposition of secrecy in a significant number of judicial proceedings dealing with the crime of human trafficking, a fact that culminates in the non-effectuation of the fundamental principle of Procedural Publicity, revealing, therefore, strong indications of unconstitutionality of the decisions rendered.